A Meta-Analysis of 80% Fraction of Inspired Oxygen on Surgical Site Infection in Patients Undergoing Surgery - Erisadana, Rifaldy Nabiel; Tohari, Achmad Ilham; Supranoto, Yehuda Tri Nugroho; Utami, Wiwien Sugih; Indreswari, Laksmi (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2023)
Background: WHO recommended the use of 80% FiO2 in patients undergoing general anesthesia with endotracheal intubation (ETI) to prevent surgical site infection (SSI). However, the ongoing debate regarding efficacy and safety raises because further trials have been published. We conducted a review based on recommendations in terms of SSI as the primary outcome and adverse events as the secondary outcome in both patients with or without ETI.Method: A literature search was carried out by PubMed, ScienceDirect, and Google Scholar for RCTs in all-type surgical patients who administrated 80% FiO2 compared with 30–35% FiO2. Pooled relative risks with a 95% confidence interval were conducted for meta-analysis. Result: Based on 23 RCTs included in the analysis, there were no significant differences in terms of SSI (RR,0.85; 95%CI, 0.72 to 1.01; p=0.07), sepsis (RR,1.47; 95%CI, 0.78 to 2.76; p=0.23), postoperative hospitalization days (PHD) (RR,0.16; 95%CI, -0.67 to 0.98; p=0.71), ICU admission (RR,0.94; 95%CI, 0.78 to 1.13; p=0.50), reoperation required (RR,0.78; 95%CI, 0.30 to 2.06; p=0.62), and 30-days mortality (RR,1.18; 95%CI, 0.76 to 1.84; p=0.45). In contrast, even though the subgroup analysis showed association that PHD longer in high FiO2 group for colorectal surgery (RR,0.80; 95%CI, 0.24 to 1.35; p=0.005), the high FiO2 significantly reduced SSI and anastomotic leakage in abdominal surgery (RR,0.78; 95%CI, 0.62 to 0.99; p=0.04 and RR,0.55; 95%CI, 0.36 to 0.85; p=0.008).Conclusion: This meta-analysis provides evidence that administration of 80% FiO2 even though association with longer of PHD in colorectal surgery, it is associated with a reduction in SSI and anastomotic leakage in patients who underwent abdominal surgery. It contrasts for sepsis, ICU admission, reoperation required, 30-day mortality, SSI, and PHD in all-type surgery.